Fundamentals of Industrial Instrumentation and Process Control, Second Edition - Dunn, William C. (McGraw-Hill Education, 2019)
A Fully Updated, Practical Guide to Automated Process Control and Measurement Systems. This thoroughly revised guide offers students a solid grounding in process control principles along with real-world applications and insights from the factory floor. Written by an experienced engineering educator, Fundamentals of Industrial Instrumentation and Process Control, Second Edition, is written in a clear, logically organized manner. The book features realistic problems, real-world examples, and detailed illustrations. You?ll get clear explanations of digital and analog components, including pneumatics, actuators, and regulators, and comprehensive discussions on the entire range of industrial processes. Fundamentals of Industrial Instrumentation and Process Control, Second Edition covers: Pressure, Flow, Temperature and heat, Humidity, density, viscosity, & pH, Position, motion, and force, Safety and alarm, Electrical instruments and conditioning, Regulators, valves, and actuators, Process control, Documentation and symbol standards, Signal transmission, Logic gates, Programmable Logic controllers, Motor control, And much more.